Cytology of the minor-vein phloem in 320 species from the subclass Asteridae suggests a high diversity of phloem-loading modes† - Batashev, Denis R.; Pakhomova, Marina V.; Razumovskaya, Anna V.; Voitsekhovskaja, Olga V. (Frontiers in Plant Science, 2013)
The discovery of abundant plasmodesmata at the bundle sheath/phloem interface in Oleaceae (Gamalei, 1974) and Cucurbitaceae (Turgeon et al., 1975) opened the questions whether these plasmodesmata are functional in phloem loading and how widespread is symplasmic loading. Analysis of over 800 dicot species allowed the definition of ‘open’ and ‘closed’ types of the minor vein phloem depending on the abundance of plasmodesmata between companion cells and bundle sheath (Gamalei, 1989; 1990). These types corresponded to potential symplasmic and apoplasmic phloem loaders, respectively; however, this definition covered a spectrum of diverse structures of phloem endings. Here, a review of detailed cytological analyses of minor veins in 320 species from the subclass Asteridae is presented, including data on several cell types and their combinations which have not been reported previously. The percentage of Asteridae species with ‘open’ minor vein cytology which also contain sieve-element-companion cell complexes with ‘closed’ cytology, i.e. that show specialization for both symplasmic and apoplasmic phloem loading, was determined. Along with recent data confirming the dissimilar functional specialization of structurally different parts of minor vein phloem in the stachyose-translocating species Alonsoa meridionalis (Voitsekhovskaja et al., 2009), these findings suggest that apoplasmic loading is indispensable in a large group of species previously classified as putative symplasmic loaders. Altogether, this study provides formal classifications of companion cells and of minor veins, respectively, in 24 families of the Asteridae based on their structural features, opening the way to a close investigation of the relationship between structure and function in phloem loading.